Scoping Review of the Scientific Production on Parenting Coordination - Asunción Tejedor Huerta; Núria Vázquez Orellana; Francisco González Sala; Macarena Tortosa Pérez (Anuario de Psicología Jurídica)

(untitled)
The aim of this study is to find out, through a review of the existing literature, the state of development and implementation of the figure of the parenting coordinator in those countries that have opted to seek more efficient methods for families that have been exposed to situations of high conflict after the breakup, as well as to determine the effectiveness of this type of action. The search for articles was carried out through the WOS database between 2008 and 2023 following the PRISMA method. The results focus on conceptual, legal and applied aspects, highlighting the effectiveness of these interventions at a legal level and in the reduction of conflict. It can be concluded that parental coordination is taking its place in family intervention in a judicial context, making it necessary for further empirical research, especially in Spain, in order to advance its implementation as an effective method.